Change in the Rate of Biological Aging in Response to Caloric Restriction: CALERIE Biobank Analysis. (22nd May 2017) - Belsky, Daniel W; Huffman, Kim M; Pieper, Carl F; Shalev, Idan; Kraus, William E
Abstract: Biological aging measures have been proposed as proxies for extension of healthy life span in trials of geroprotective therapies that aim to slow aging. Several methods to measure biological aging show promise but it is not known if these methods are sensitive to changes caused by geroprotective therapy. We conducted analysis of two proposed methods to quantify biological aging using data from a recently concluded trial of an established geroprotector, caloric restriction. We obtained data from the National Institute on Aging CALERIE randomized trial through its public-access biobank (https://calerie.duke.edu/ ). The CALERIE trial randomized N = 220 nonobese adults to 25% caloric restriction ( n = 145; 11.7% caloric restriction was achieved, on average) or to maintain current diet ( n = 75) for 2 years. We analyzed biomarker data collected at baseline, 12-, and 24-month follow-up assessments. We applied published biomarker algorithms to these data to calculate two biological age measures, Klemera–Doubal Method Biological Age and homeostatic dysregulation. Intent-to-treat analysis using mixed-effects growth models of within-person change over time tested if caloric restriction slowed increase in measures of biological aging across follow-up. Analyses of both measures indicated caloric restriction slowed biological aging. Weight loss did not account for the observed effects. Results suggest future directions for testing of geroprotective therapies in humans.